PENINGKATAN BUDAYA LITERASI DENGAN PELATIHAN MENULIS PUISI DI SMA MUHAMMADIYAH 3 KOTA TANGERANG - Ariyana, Ariyana; Ramdhani, Intan Sari; Anggraini, Nori (Community Services and Social Work Bulletin, 2021)
Writing quality poetry requires good ideas and imagination, this can be obtained by getting used to it through literacy culture. There are still many students who are not familiar with literacy, this is because they are used to knowing something, it is enough to just look at the applications on the device without reading with understanding, so the results obtained are not optimal. Based on this, the Community Service lecturer team followed up on problems in the field. One of the efforts made to improve literacy culture is by holding poetry writing training at SMA Muhammadiyah 3 Tangerang City. The method used in implementing this community service is the productive method. The productive method used is by producing literary works in the form of poetry with a literacy culture. This service activity is divided into three stages, namely the preparation, implementation, and evaluation stages. Students are very enthusiastic about participating in online poetry writing training. This is evidenced by several questions posed to the informants. Students who were previously unfamiliar with a variety of poetry became more aware of the genre of poetry so that they could understand which type of poetry was made.